Emissions trading : a way of achieving the climate goal : summary of the final proposal found in SOU 2000:45 (Statens offentliga utredningar, ISSN 0375-250X, 2000)
Summary (s. 7-12).
Keywords: ilmansuojelu : Ruotsi; päästökauppa; Kioton sopimus